The neuroscience of religious experience - McNamara, Patrick, 1956- (Cambridge ; New York : Cambridge University Press, 2009)
Technical advances in the life and medical sciences have revolutionised our understanding of the brain, while the emerging disciplines of social, cognitive, and affective neuroscience continue to reveal the connections of the higher cognitive functions and emotional states associated with religious experience to underlying brain states. At the same time, a host of developing theories in psychology and anthropology posit evolutionary explanations for the ubiquity and persistence of religious beliefs and the reports of religious experiences across human cultures, while gesturing toward physical bases for these behaviours. What is missing from this literature is a strong voice speaking to these behavioural and social scientists - as well as to the intellectually curious in the religious studies community - from the perspective of a brain scientist. --from publisher description
God and the self -- On the self and the divided self -- Mechanisms and dynamics of decentering -- Neurology of the self -- Neurology of religious experiences -- Neurochemistry of religiosity -- Self-transformation as a key function of performance of religious practices -- Self-transformation through spirit possession -- God concepts -- Religious language -- Ritual -- Life-span development of religiosity and the self -- The evolution of self and religion
Includes bibliographical references and index
Keywords: Psychology, Religious; Evolutionary psychology